Perspectives on the non-jurisdictional protection of the human right to housing in Mexico - Venegas Agüeros, Mayra Patricia (2021)
This article will address the role that Public Organizations Protecting Human Rights have performed in relation to the protection of the right to housing.  From our perspective, it is necessary to reinforce all the means of protection of the human right to housing, in this case, in regards to the non-jurisdictional protection carried out by Public Organizations Protecting Human Rights.  In the present essay we will touch on the main scopes and achievements that have stood out in the protection of the human right to housing, in accordance with the constitutional and conventional standards that are pertinent to the case.  So that in the end, we can take stock of what a more effective protection of human rights implies, from the non-jurisdictional sphere, in accordance with the challenges that the right to housing implies for people in vulnerable situations.